Iggy the legend - Barrows, Annie; Ricks, Sam (2022)
"When Iggy needs to make a bit of money, he conjures up a scheme to help kids con the Tooth Fairy for profit"--
Ages 8-12.
Keywords: Moneymaking projects -- Fiction; Schools -- Fiction